Geometrical tuning of thermal phonon spectrum in nanoribbons. (17th February 2016) - Ramiere, Aymeric; Volz, Sebastian; Amrit, Jay
Abstract: Phonon spectral energy transmission in silicon nanoribbons is investigated using Monte-Carlo simulations in the boundary scattering regime by changing the length and width geometrical parameters. We show that the transition frequency from specular scattering to diffuse scattering is inversely proportional to the edge roughness with a geometry independent factor of proportionality. The increase of the length over width ratio leads to a decrease of the energy transmission in the diffuse scattering regime which evolves as . This trend is explained by developing a model of phonon energy transmission in the fully diffuse scattering regime which takes into account the probability for a diffusively scattered phonon to be directly transmitted from any position on the edge of the nanoribbon. This model establishes the importance of the solid angles in the energy transmission evolution with . The transition from unity energy transmission in the specular scattering regime to reduced transmission in the diffuse scattering regime constitutes a low-pass frequency filter for phonons. Our simulations show an energy rejection rate better than 90% for high, which paves the way for potential high performance filters. Filtering out high frequency phonons is of significant interest for phononic crystal applications, which use band engineering of phonons in the wave regime with low frequencies.